Télémonitorage des grandes fonctions physiologiques chez les primates vigiles - Guy Germain (Revue de Primatologie)
The common difficulties of the study of nonhuman primates are close to the constraints encountered in implementing the principles of human telemedicine. They stem from the remote localization of animals and of their geographical dispersion, in field studies. They also stem from the need to control in the laboratory, experimental treatments with a minimal disturbance of their social behavior. Radio waves are an excellent transmission signal to monitor the animals because they can spread information rapidly and over long distances through the air. All telemetry devices operate on the same basic principle which consists in one or more sensors coupled to a radio-encoder transmitter and an antenna system coupled to an analog or digital, receiver-decoder. Progress in remote transmission also stems from the miniaturization of electronic emitting- and acquisition-devices that are less energy demanding and therefore have much greater transmission range and autonomy. Many telemetric devices, often totally implantable in the body of the animal, are now commercially available. They allow detailed monitoring of physiological parameters of the cardiovascular, nervous, musculoskeletal, metabolic, respiratory and reproductive systems in nonhuman primates entirely free of their movements. They are widely used in pharmacology and toxicology studies. Others devices still at the experimental state, also include the combination of telemetric recordings of pressure, muscle biopotentials, nerve biopotentials or temperature, with audio and video signals that can themselves be transferred by telemetry. The development of future systems will probably focus on the increasing need for characterizing highly mobile individuals or groups of animals in complex environments using the least invasive methods. These systems should help characterizing the trends of certain physiological states (ethophysiological studies, field studies) or pathophysiologic states (pathology, pharmacology) quickly enough to alert the observers so that they can apply feedback corrective actions when necessary. Whole domains of major physiological functions such as metabolic and hormonal regulations cannot yet be explored directly by telemetry. More advanced concepts such as hormonal or metabolic biosensors are being validated in the laboratory and could become accessible to telemetric acquisition in the future.